Branding Suspense: The Audiovisual Construction of Alfred Hitchcock as a Media Icon - García, César; Flores, Maria Sierra; Barberá, Rafael (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This paper explores Alfred Hitchcock’s pioneering use of visual media to construct a personal brand that transcended the role of film director and established him as a cultural icon. Drawing on visual methodologies and a qualitative biographical approach, the study argues that Hitchcock exemplifies a form of proto-visual branding, using narrative and aesthetic cohesion across media platforms to maintain both popular appeal and critical legitimacy. By examining the visual rhetoric embedded in his marketing materials and media appearances, the article reveals how Hitchcock turned himself into an enduring multimedia symbol.